Symptomatic Primary Hyperparathyroidism as a Risk Factor for Differentiated Thyroid Cancer. (18th November 2018) - Vargas-Ortega, Guadalupe; Balcázar-Hernández, Lourdes; González-Virla, Baldomero; Ramírez-Rentería, Claudia; Nieto-Guzmán, Oriana; Garrido-Mendoza, Ana Pamela; Flores-Maya, Marco Antonio; Mercado, Moisés; Victoria, Mendoza-Zubieta
Abstract : Background . The primary hyperparathyroidism (PHPT) is a common disease for the endocrinologist. The concomitant thyroid disease and differentiated thyroid cancer (DTC) appear to be more frequent in patients with PHPT than in the general population. The aim of this study was to characterize patients with symptomatic PHPT with and without DTC and analyze frequency and risk factors. Methods . We consecutively studied patients with symptomatic PHPT diagnosed and treated at our center between 2013 and 2015. Patients with subclinical and syndromic forms of PHPT were excluded. Clinical and biochemical characteristics of patients with and without DTC were compared and risk factors were determined. All patients were studied with thyroid ultrasound and thyroid gammagraphy with TC-MIBI. Two expert surgeons performed all the surgical procedures. Results . In 59 patients included, we found 12 cases of PTC (20.3%). The final histopathological report of the PTC was 7 cases of follicular variant, 2 cases of oncocytic variant, 2 cases of classic variant, and 1 case of columnar cells variant of PTC. Patients with thyroid cancer were older than patients without thyroid cancer (62 ± 9.5 versus 52 ± 15.8, p = 0.03). Higher preoperative levels of iPTH were associated with PTC (p=0.03) [OR 5.16 (95% CI: 1.08-24.7)]. Conclusion . PTC is frequent in patients with symptomatic PHPT. Thyroid nodules in patients with symptomatic PHPT must be studied before parathyroidectomy. In symptomatic PHPT, higher level concentration of parathormone (PTH) was associated with higher risk of DTC.